Persepsi Peternak Terhadap Pemeliharaan Sapi Sonok di Madura - Slamet Widodo; Na'riful Ilmiah (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2022)
Madura island is one area that has potential in the farm sector. Madura cattle are classified into three categories: beef cattle, sonok cattle, and karapan cattle. The high cost of raising sonok cattle is an obstacle for farmers with middle and lower-middle financial conditions. This can be considered to affect the perception of farmers about raising sonok cattle. The purpose of this study is to analyze the perception of farmers on the maintenance of sonok cattle and the factors that influence it. The research was conducted in Waru Barat Village, Waru District, Pamekasan Regency. The study was conducted from October to November 2021. The respondents in this study were 30 sonok cattle breeders, considering that the number was already considered representative. The snowball sampling technique determined the determination of respondents. The data were descriptively analyzed using a Likert scale before moving on to multiple linear regression analysis. The results of this study indicate that 90% of farmers have a productive age with a low level of education, as much as 94%, experience > 20 years as much as 57%, and income below the East Java Poverty Line Index (IGK). The perception of farmers is classified as moderate (70%). Farmers' ideas about raising sonok cattle are affected by their level of education and experience.